Urban exploration v post-industriálnej metropole - Šimová, Terézia (Lidé města, 2016)
This text deals with the urban phenomenon known as urban exploration which has been studied in the teritory of Bratislava metropolis. The aim of this study was to describe how urban explorers understand, define and record the explored urban environment and also how they shape relationship to specific spaces of the city and city areas. The crucial part of this text consist of an analysis of ethnographic interviews with urbexers from Bratislava. Method of analysis was inspired by grounded theory by adding new dimension characteristic for urban exploration – self-identification and perception of public and private space in the metropolis. The text shows that the practice of urban exploration leads to the development of urban awareness and reinvisioning of the postmodern metropolis.